Survey on common practice in management of preeclampsia by obstetricians - Chavan, Komal; Chavan, Niranjan; Rajput, Hitendrasing D.; Mirza, Hera; Venkateswaran, Sneha; Mahapatra, Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Approximately 72,000 pregnant women all over the world die every year due to direct or indirect complications related to eclampsia and severe preeclampsia. Incidence of hypertensive disorders in pregnancy in India is found to be 10.08% as per the data collected by the National Eclampsia Registry (NER). Here we present the results of a survey conducted among obstetricians in India to know the common practices in the management of pre-eclampsia followed in our country. Methods: Observational study of survey which was conducted for the period of 1 month from 22nd May 2020 to 22nd June 2020. Questionnaire was prepared on surveyheart.com and sent to obstetricians via Social media platforms to the members of FOGSI. all answers 'collected' and results were prepared from given answers. The survey was answered online by 289 obstetricians. Results: For mild to moderate pre-eclampsia Labetalol is still first line antihypertensive agent being used by many of the obstetricians. In our study also we found out Tab Labetalol 100mg BD is the most preferred type (278, 96.19%) of first line anti-hypertensive in cases of pre-eclampsia followed by Cap Nifedipine 5mg QID and Tab Amlodipine 5mg OD respectively. Conclusions: Comprehensive educational efforts and skill building modules are need of hour to keep every practicing obstetrician regarding recent advances in standard practice protocols.With close monitoring of all cases and well selected anti-hypertensive treatment, it is possible to achieve favourable outcomes for the mother and the baby.